Characterization of rosacea patients in Tohoku area of Japan: Retrospective study of 340 rosacea cases. Issue 5 (17th February 2022) - Wada‐Irimada, Moyuka; Yamamoto, Haruka; Terui, Hitoshi; Omori‐Shimada, Ryoko; Yamazaki, Emi; Kikuchi, Katsuko; Aiba, Setsuya; Yamasaki, Kenshi
Abstract: Rosacea is a chronic inflammatory skin disease with facial redness and acne‐like papules and pustules. The characteristics and background of rosacea patients in Japan have not been well documented. In this study, we retrospectively collected the medical information of rosacea patients, and investigated the background, complications, exacerbating factors, and status of allergy. Between January 2010 and December 2020, 431 cases were diagnosed as rosacea or rosacea‐like dermatitis. We selected 340 patients, in which we could confirm telangiectasia on facial skin. Females and males numbered 266 and 74, respectively. The average age of the first visit was 51.5 years, and the youngest and oldest were 11 and 88 years old. Among 340 cases, 323 had erythematotelangiectatic rosacea, 97 papulopustular rosacea, 20 phymatous rosacea presenting as rhinophyma, and four had symptoms of ocular rosacea. The most common complication was hay fever (93 individuals, 27.4%), and 66 (19.4%) had a medical history of contact dermatitis. Temperature differences (141 individuals, 41.5%) were the most common exacerbating factor followed by sunlight exposure (60 individuals, 17.6%). Seventy‐eight individuals received allergen‐specific immunoglobulin (Ig)E tests, and IgE for cedar was the most frequently observed (46 individuals, 59.0%). High frequencies of IgE for Dermatophagoides pteronyssinus or D. farinae (33 individuals, 42.3%) and house dust I (31 individuals, 39.7%) suggested that environmental conditions at home would affect rosacea symptoms. Since the facial skin is exposed to environmental stimuli every moment, this retrospective observation suggested the importance of the daily lifestyle guidance as well as medical treatments.